Activating 'language for learning' through schoolwide pedagogy: The case of MacKillop School. (July 2013) - O'Neill, Shirley
This article presents a case study of a primary school that engaged with theI nnovativeD esigns forE nhancingA chievement inS chools (IDEAS) Project, and moved to the sustaining phase over a period of three years. It reports how the students, who were 98 percent English as a second language, improved their reading and numeracy during this time and investigates staff perceptions of the reasons why. It also considers how the school's practices particularly exemplify two of the six IDEAS Project criteria for the development of a schoolwide pedagogy (SWP). These are the need to honour the distinctive features and needs of the school's student community and the requirement for it to be informed by authoritative educational theories and research. The school's SWP, termed 'active pedagogy' and its principles are explored, along with its implementation and perceived impact on teaching and learning. The case study raises the issue and importance of teachers' and students' mutual use of a common language for learning. A preliminary definition of this is offered and the school's improvement experience is further explored through the development of a concept map.